LANGUAGE ATTITUDES TOWARDS WRITTEN ALAY VARIETY IN FACEBOOK INTERACTION - Astuti, Widya (2013)
This research paper entitled Language Attitudes towards Written 'Alay' Variety in Facebook Interaction aims to reveal the use of the alay variety in Facebook media and the attitudes of users and ex-users of the variety. The study employs a descriptive method to describe and interpret the data. As the writer mainly divides the study into two aspects: linguistic feature of alay variety and the language attitudes towards the variety, the study applies Crowley's theory of language change (1999) and Ryan's (1982) and Anderson's (1991) theory of language attitudes. The study reveals that the realization of written alay variety in Facebook covers two broad categories, namely spelling and writing modifications. The spelling modifications in written alay variety were found to occur in five different cases, spelling shift, spelling addition, spelling deletion, contraction, and irregular spelling modification. Related to language attitudes toward the written alay variety, users and ex-users develop different attitudes towards the use of alay variety. Users tend to have more neutral attitudes to the use of alay variety; they develop more positive attitudes towards the variety. In contrast, most ex-users react negatively towards the use of alay variety because they consider the variety to have a low prestige or status and is not a proper variety to use. ABSTRAK Penelitian berjudul Language Attitudes towards Written 'Alay' Variety in Facebook Interaction ini dimaksudkan untuk mengungkap penggunaan variasi alay di media Facebook dan sikap pengguna serta mantan pengguna variasi tersebut. Penelitian ini menggunakan metode deskriptif dalam menjelaskan dan menginterpretasikan data. Dengan pertimbangan bahwa penulis membagi penelitian ini kedalam dua aspek, yaitu fitur liguistik dan sikap bahasa terhadap variasi, penelitian ini menggunakan teori milik Crowley tentang perubahan bahasa (1999) serta teori milik Ryan (1982) dan Anderson (1991) mengenai sikap bahasa. Penelitian ini mengungkap bahwa perwujudan variasi alay di Facebook meliputi dua kategori besar, yaitu, modifikasi pada ejaan dan tulisa. Modifikasi pada ejaan ditemukan terjadi pada lima kasus yang berbeda, yaitu, spelling shift (pergeseran ejaan), spelling addition (penambahan ejaan), spelling deletion (penghapusan ejaan), contraction (kontraksi), dan irregular spelling modification (modifikasi ejaan yang tidak beraturan). Berkaitan dengan sikap bahasa terhadap variasi alay, pengguna dan mantan pengguna memiliki sika yang berbeda terhadap penggunaan variasi tersebut. Pengguna cenderung memiliki sikap yang netral terhadap variasi alay; mereka memiliki sikap yang lebih positif. Sebaliknya, kebanyakan mantan pengguna merespon secara negative terhadap penggunaan variasi alay karena mereka menganggap variasi tersebut berstatus rendah dan bukan merupakan variasi yang pantas untuk digunakan.